Exchange rate movements and export market dynamics: Evidence from China - Xiaobing Huang (Kiel Institute for the World Economy (IfW), 2017)
This paper highlights the relationship between foreign exchange rate fluctuations and firms' export market dynamics using a Chinese firm-level production data and a firm-level trade data over the period of 2000-2006. The author adopts a discrete-time survival model in his empirical investigation and further executes several extensions and robustness checks to the baseline results. The main results of the paper can be summarized as follows: First, an exchange rate appreciation increases the likelihood of export market exit, reduces the capability of export market survival and decreases the probability of export market entry. Second, high productivity firms are less likely to exit from export markets and more likely to enter and survive in export markets in the period of exchange rate appreciation. Third, exchange rate appreciation decreases the likelihood of export market entering and increases the likelihood of export market exiting more for private-owned firms, young firms and non-eastern firms. Finally, other sources of heterogeneity, such as extensive margins, import demand elasticity, different destinations, U.S. dollar peg, and the liberalization of trading rights also matter regarding the effect of exchange rate changes.
Keywords: F14; F31; F32; F41; 330; exchange rate movements; export market dynamics; firm heterogeneity; China